2020
DOI: 10.1136/annrheumdis-2020-217070
|View full text |Cite
|
Sign up to set email alerts
|

Remission in systemic lupus erythematosus: testing different definitions in a large multicentre cohort

Abstract: ObjectivesRemission in systemic lupus erythematosus (SLE) is defined through a combination of ‘clinical SLE Disease Activity Index (cSLEDAI)=0’, ‘physician's global assessment (PGA) <0.5’ and ‘prednisone (PDN) ≤5 mg/day’. We investigated the performance of these items, alone or in combination, in defining remission and in predicting SLICC/ACR Damage Index.MethodsWe tested seven potential definitions of remission in SLE patients followed-up for ≥5 years: PDN ≤5 mg/day; PGA <0.5; cSLEDAI=0; PGA <0.5 plu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 26 publications
(22 reference statements)
4
24
0
Order By: Relevance
“…In an Italian multicentre study based on a larger cohort of patients (n=646), the performance of seven different definitions of remission was tested. 20 Clinical SLEDAI=0 had the best performance in terms of protection against damage compared with the other definitions including PGA ≤0.5 or prednisolone ≤5 mg/day. ► Data from the Asia-Pacific Lupus Collaboration cohort were reviewed.…”
Section: Epidemiology and Outcomesmentioning
confidence: 88%
“…In an Italian multicentre study based on a larger cohort of patients (n=646), the performance of seven different definitions of remission was tested. 20 Clinical SLEDAI=0 had the best performance in terms of protection against damage compared with the other definitions including PGA ≤0.5 or prednisolone ≤5 mg/day. ► Data from the Asia-Pacific Lupus Collaboration cohort were reviewed.…”
Section: Epidemiology and Outcomesmentioning
confidence: 88%
“…Controversies exist (9,15), however, and to date, only a few clinical trials have evaluated the impact of treatment strategy on rates of remission. Recently, research comparing different remission definitions was conducted by Saccon et al (48). They indicated that a clinical SLEDAI score of 0 is an easy‐to‐achieve definition with the best performance in predicting damage progression compared to other definitions, including PhGA and low‐dose prednisone.…”
Section: Discussionmentioning
confidence: 99%
“…In a post-hoc analysis carried out in patients enrolled in BLISS-52 and BLISS-76, remission and LDA were able to discriminate response to belimumab 10 mg/kg from placebo. 5 6 Notably, clinical (c) SLEDAI-2K=0 was the best discriminator 6 and, importantly, in a recent multicentre cohort study including 646 patients, cSLEDAI=0 had the best performance in predicting damage accrual compared with all other definitions of remission. 7 In real-life the proportion of patients who can achieve a stable low lupus disease activity state (LLDAS) and remission was higher than that obtained in randomised controlled trials, as shown in two recent studies.…”
Section: Learning Objectivesmentioning
confidence: 98%